A review on use of computational biology in testing of skeletal muscle function in COPD patients (Journal of Pharmaceutical Negative Results, 2022)
Computer biology and bioinformatics are interdisciplinary fields that develop and apply computational methods to analyse large amounts of biological data, such as genetic sequences, cell populations, or protein samples, in order to make new predictions or find novel biology. Analytical approaches, mathematical modelling, and simulation are among the computational methods employed.Chronic Obstructive Pulmonary Disease (COPD) is a lung inflammatory disease that causes persistent airflow restriction. These individuals frequently have extensive systemic consequences, such as skeletal muscle dysfunction, which severely restrict their life expectancy. Despite extensive research, the molecular basis of muscle deterioration in COPD remains a matter of contention. We used a network biology approach to investigate the link between the molecular and physiological responses of muscles to training and systemic inflammatory mediators in this study. Failure to coordinately activate expression of various tissue remodelling and bioenergetics pathways is a distinctive feature of COPD diseased muscles, according to our model. Our findings also point to a relationship between this phenomena and aberrant expression of a number of histone modifiers, which we discovered associated with oxygen utilisation. These findings highlighted the intriguing hypothesis that cell hypoxia is a crucial contributor in COPD patients' skeletal muscle.